The situation in Syro-Palestine prior to the Exodus conquest/settlement as reflected in the Amarna Letters - Westhuizen, J. P. Van der (Journal for semitics, 1995)
The Amarna letters - the correspondence from the Syro-Palestine vassals to the Egyptian court/pharaoh - directly and indirectly reveal the situation in Syria and Palestine before the Exodus-event.